Full-arch implant rehabilitation - Garg, Arun K. ([S.l.] : Quintessence Publishing Co, Inc., 2019)
The full-arch implant rehabilitation (FAIR) protocol is one of the newest implant therapy innovations to treat the edentulous or nearly edentulous patient. The FAIR prosthesis is immediate, fixed, esthetically pleasing, highly functional, inexpensive, and maintainable, and it can frequently be installed without bone grafting. This book describes how the FAIR protocol works, who it should be used for, and methods to implement it successfully for different patients. The system can be used in both arches and in patients with total or near-total edentulism. Several chapters are devoted to describing step-by-step treatment with detailed clinical photographs documenting every step from initial assessment to prosthesis delivery. Even those new to fixed denture systems will find the procedures easy to follow and can begin implementing the FAIR approach for their patients.
Full-arch implant rehabilitation -- Contents -- Preface -- Chapter 1: Evolution of the FAIR Protocol -- Chapter 2: History of Tilted Implants with an Immediate Prosthesis -- Chapter 3: Identifying and Evaluating Candidates -- Chapter 4: The FAIR Technique and Its Modifications -- Chapter 5: Treating the Fully Edentulous Maxilla -- Chapter 6: Treating the Fully Edentulous Mandible -- Chapter 7: Treating the Partially Edentulous Maxilla -- Chapter 8: Treating the Partially Edentulous Mandible -- Chapter 9: FAIR Prosthetics -- Chapter 10: Possible Complications.
Includes bibliographical references and index.
Keywords: Dental Implantation -- methods; Jaw, Edentulous -- surgery; Dental Implants; Dental Arch